1989
DOI: 10.1159/000195735
|View full text |Cite
|
Sign up to set email alerts
|

Role of Lactic Acidosis in the Ventilatory Response to Heavy Exercise

Abstract: The purpose of this study was to determine the role of lactic acidosis in the ventilatory response to heavy exercise above anaerobic threshold. Seven subjects ingested either NaHCO3 or CaCO3 at a dose of 300 mg/kg body weight and ran on a motor-driven treadmill at a work load corresponding to 90% of VO2max and above anaerobic threshold for a period of 5 min while minute ventilation and PetCo were recorded breath by breath. A total of 10 runs, 5 with CaCO3 Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

1989
1989
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 18 publications
(21 reference statements)
0
4
0
Order By: Relevance
“…Wassermann and Whipp (1975) reported a close relationship between RCP and metabolic acidosis: however, numerous investigators have challenged the causal relationship between hyperventilation and lactic acidosis (Hagberg et al 1982;Heigenhauser at al. 1983;Gaesser et al 1984;Jeyaranjan et al 1989;Busse et al 1992). Correlations observed between metabolic and respiratory markers have often been suggested to be coincidental.…”
Section: Discussionmentioning
confidence: 99%
“…Wassermann and Whipp (1975) reported a close relationship between RCP and metabolic acidosis: however, numerous investigators have challenged the causal relationship between hyperventilation and lactic acidosis (Hagberg et al 1982;Heigenhauser at al. 1983;Gaesser et al 1984;Jeyaranjan et al 1989;Busse et al 1992). Correlations observed between metabolic and respiratory markers have often been suggested to be coincidental.…”
Section: Discussionmentioning
confidence: 99%
“…However, new aspects are turning up, especially regarding the relative role of individual stimuli. For example a recent study by Jeyaranjan, Goode & Duffin (1989) has seriously challenged the widely accepted concept about the role of lactic acid in the ventilatory response to heavy exercise. This study has shown that other factors, perhaps of neurogenic origin, must also be involved in regulation of breathing under these conditions.…”
Section: Introductionmentioning
confidence: 99%
“…We conclude that EFL or even impending EFL during heavy and maximal exercise and with added dead space in fit subjects causes EELV to increase, reduces the VT, and constrains the increase in respiratory motor output and ventilation. dead space; helium-oxygen; feedback inhibition; respiratory muscle loading/unloading THE HYPERVENTILATORY response to high-intensity exercise has been attributed to one or more neurohumoral stimuli (4,6,16). There is also some indirect evidence that these ventilatory responses may be influenced by the mechanical constraints presented by the airways and/or inspiratory muscles, at least in many highly fit subjects capable of achieving higher than normal maxi-mal metabolic rates and minute ventilations (V E) (17,28).…”
mentioning
confidence: 99%